2022
DOI: 10.34172/ahj.2022.1354
|View full text |Cite
|
Sign up to set email alerts
|

Hookah Smoking among Brazilian University Students: An Exploratory Survey on the Prevalence and Perceptions of Addiction and its Harmfulness

Abstract: Background: This study aimed to determine the prevalence, beliefs, attitudes, and perceptions of hookah use in a population of undergraduate students at a large public university in Brazil. Methods: The sample consisted of 1348 undergraduate students aged over 18-year-old. They completed structured questionnaires on demographic information and close-ended questions on the past and current experiences of smoking hookah. The data underwent descriptive analysis and binary logistic regression. Findings: Finally, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…Nevertheless, adoption of the WHO FCTC paved the way for taking serious measures to access such data. [48][49][50] While intangible costs were not considered in most of the studies, such as those related to premature mortality, the reported costs attributable to tobacco use were substantial. Notably, a recent study in Australia reported that intangible costs accounted for nearly 85% of the total social costs of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adoption of the WHO FCTC paved the way for taking serious measures to access such data. [48][49][50] While intangible costs were not considered in most of the studies, such as those related to premature mortality, the reported costs attributable to tobacco use were substantial. Notably, a recent study in Australia reported that intangible costs accounted for nearly 85% of the total social costs of smoking.…”
Section: Discussionmentioning
confidence: 99%
“…This design was deemed suitable as it does not seek to change things but describe events as they naturally occur. This study design has been used in various parts of the country [3][4][5] and globally [18][19] on the same topic and has aided in achieving prevalence rates as well as perceptions, as per the current study objectives.…”
Section: Methodsmentioning
confidence: 99%